Synthesis and Antimicrobial Activity of Some Derivatives on the Basis (7-hydroxy-2-oxo-2H-chromen-4-yl)-acetic Acid Hydrazide - Elizabeth Has-Schon (Molecules, 2006)
(7-Hydroxy-2-oxo-2H-chromen-4-yl)-acetic acid hydrazide (2) was prepared from (7-hydroxy-2-oxo-2H-chromen-4-yl)-acetic acid ethyl ester (1) and 100% hydrazine hydrate. Compound 2, is the key intermediate for the synthesis of several series of new compounds such as SchiffÃ¢Â€Â™s bases 3a-l, formic acid N'-[2-(7-hydroxy-2-oxo-2H- chromen-4-yl)acetyl] hydrazide (4), acetic acid N'-[2-(7-hydroxy-2-oxo-2H-chromen-4- yl)-acetyl] hydrazide (5), (7-hydroxy-2-oxo-2H-chromen-4-yl)-acetic acid N'-[2-(4- hydroxy-2-oxo-2H-chromen-3-yl)-2-oxoethyl] hydrazide (6), 4-phenyl-1-(7-hydroxy-2- oxo-2H-chromen- 4-acetyl) thiosemicarbazide (7), ethyl 3-{2-[2-(7-hydroxy-2-oxo-2H- chromen-4-yl)-acetyl]hydrazono}butanoate (8), (7-hydroxy-2-oxo-2H-chromen-4-yl)- acetic acid N'-[(4-trifluoromethylphenylimino)methyl] hydrazide (9) and (7-hydroxy-2- oxo-2H-chromen-4-yl)acetic acid N'-[(2,3,4-trifluorophenylimino)-methyl] hydrazide (10). Cyclo- condensation of compound 2 with pentane-2,4-dione gave 4-[2-(3,5- dimethyl-1H-pyrazol-1-yl)-2-oxoethyl]-7-hydroxy-2H-chromen-2-one (11), while with carbon disulfide it afforded 7-hydroxy-4-[(5-mercapto-1,3,4-oxadiazol-2-yl)methyl]-2H- chromen-2-one (12) and with potassium isothiocyanate it gave 7-hydroxy-4-[(5- mercapto-4H-1,2,4-triazol-3-yl)methyl]-2H-chromen-2-one (14). Compound 7 was cyclized to afford 2-(7-hydroxy-2-oxo-2H-chromen-4-yl)-N ÃŒÂ-(4-oxo-2-phenylimino- thiazolidin-3-yl) acetamide (15).